Identity and rationality in Sharia economic practice: A study at Arrahmah Sharia Consumer Cooperative, South Kalimantan Province - Hafizah, Yulia; Nilasari, Erissa; Syarqawie, Fitriana; Jahra, Pati Matu; Noorwahidah, Noorwahidah (Universitas Islam Indonesia, 2024)
IntroductionThe Sharia consumer cooperative is one of the many legal forms of Islamic economic activity in Indonesia, including South Kalimantan Province. However, studies on the identity and rationality of this practice are still limited.ObjectivesThis research aims to understand how Islamic identity influences economic decisions and how Sharia economic rationality is reflected in the practices of consumer cooperatives. The selection of Arrahmah Sharia Consumer Cooperative (Koperasi Konsumen Syariah Arrahmah) as the subject of the study is based on the institution's claim to be